(untitled) (The Pakistan Development Review, 1970)
Ball in his book combines wage push and demand pull by making wages and aggregate expenditures functions of the same variable, expected profit. The expected profit (which is related to profits of the previous period) is a function of the level and the rate of change of unemployment. With a given level of profits of the last period, the expected level of profits is negatively related to the current level of unemployment and the change in unemployment. The expected level of profits stands as an index of the expected rate of inflation, on the assump¬tion that the money profits of enterprises will rise in inflationary conditions. The expected level of profits also affects the decisions of firms in dividing their assets between cash balances and real-capital assets. An increase in expected profits increases aggregate expenditures through an expansion of investment (gross investment measured in money terms) and a reduction of business money holdings, which raises income velocity. An increase in aggregate expenditure and output leads to an upward movement in the expected profits function. But this further increase in expected profit does not continue without an upper limit, especially when all idle-money balances have been activated or interest rate rises fast enough. Therefore, the expansion stops unless the money supply increases. The analysis takes the supply of nominal money as exogenously determined by the decision of the monetary authorities; it is initially assumed to be constant.